2008
DOI: 10.1007/s00464-008-9867-2
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of ambulatory versus inpatient laparoscopic cholecystectomy

Abstract: Ambulatory laparoscopic cholecystectomy can be performed safely for selected patients, with reduced cost and a high level of patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
58
1
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 43 publications
2
58
1
3
Order By: Relevance
“…Nevertheless, the medical cost was significantly higher [26]. In Taiwan, the average length of hospital stay for open and laparoscopic cholecystectomy is 13.1 and 4.9 days, Analysis of gallstone disease after gastric cancer surgery respectively, which is longer than that reported in other countries, not to mention those performing laparoscopic cholecystectomy as an outpatient procedure [19,27]. The longer hospital stay in Taiwan may be related to the different treatment protocol or cultural difference [19].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the medical cost was significantly higher [26]. In Taiwan, the average length of hospital stay for open and laparoscopic cholecystectomy is 13.1 and 4.9 days, Analysis of gallstone disease after gastric cancer surgery respectively, which is longer than that reported in other countries, not to mention those performing laparoscopic cholecystectomy as an outpatient procedure [19,27]. The longer hospital stay in Taiwan may be related to the different treatment protocol or cultural difference [19].…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic cholecystectomy performed safely in an ambulatory setting has become widely popular and accepted [19,20]. Our LOS was primarily 1-2 days, with more than half of the patients discharged in the ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
“…2 In our district general hospital, laparoscopic cholecystectomy is performed both electively for symptomatic gallstone disease, and also as an emergency procedure during an acute admission. Previous studies have reported 30-day re-admission rates of 2-5% following elective laparoscopic cholecystectomy, 3,4 and 6% following emergency laparoscopic cholecystectomy. 5 However, in our experience, patients can present with symptoms several weeks after laparoscopic cholecystectomy, and there is little data regarding re-admission rates after 30 days' postoperatively.…”
mentioning
confidence: 94%